2013
DOI: 10.1074/jbc.m113.454470
|View full text |Cite
|
Sign up to set email alerts
|

Auto-ubiquitination of Mdm2 Enhances Its Substrate Ubiquitin Ligase Activity

Abstract: Background: Mdm2, the principal ubiquitin ligase for the tumor suppressor p53, also ubiquitinates itself, but the consequences are unclear. Results: Auto-ubiquitination enhances Mdm2 binding to ubiquitin-conjugating enzymes (E2s) and its ability to ubiquitinate p53. Conclusion: Increased E2 recruitment by auto-ubiquitinated Mdm2 may enable processivity of substrate ubiquitination. Significance: Auto-ubiquitination may be a general mechanism for the activation of ubiquitin ligases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 32 publications
2
57
0
Order By: Relevance
“…and B). Moreover, MDM2 functioning as an E3 ubiquitin-protein ligase and proteasome activator [30], caused the degradation of p53 by protein polyubiquitination in miR501-5p-overexpressing KJ29 cells (Fig. 3C).…”
Section: Genementioning
confidence: 96%
“…and B). Moreover, MDM2 functioning as an E3 ubiquitin-protein ligase and proteasome activator [30], caused the degradation of p53 by protein polyubiquitination in miR501-5p-overexpressing KJ29 cells (Fig. 3C).…”
Section: Genementioning
confidence: 96%
“…One such ligase is mouse double minute (Mdm2), which can direct its own ubiquitylation and subsequent proteasomal degradation (Ranaweera and Yang, 2013). In parallel, it has also been reported that the histone acetyl transferase p300-CBP-associated factor (PCAF, also known as KAT2B) ubiquitylates Mdm2, resulting in its proteasomal degradation (Linares et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Yet despite intensive study, a role of DUBs in controlling MKRN1 stability has not been described. Our data suggest that autoubiquitination of MKRN1 could be an important control mechanism, as it is for MDM2, another p53 ubiquitin ligase 59 . Among the new substrates we identified, we found multiple transcription factors (n=7) and proteins involved in RNA metabolism (n=12).…”
Section: Discussionmentioning
confidence: 70%